YOUTH, MEDIA AND INSECURITY: THE ROLE OF SOCIAL MEDIA IN SOLVING INSECURITY CHALLENGES IN NORTHERN NIGERIA - Ibrahim Baba; Rio Baviga; Gampo Haryono (CV. Visionary Raya Sakti, 2026)
Social media is a form of mass media communication on the Internet that allows users to share information, ideas, and opinions. Social media plays a multifaceted role in modern society, impacting how we communicate, connect, consume information, and engage in cultural and societal problem-solving. In this paper, efforts have been made to focus on the contributions of these social media platforms, especially Facebook, to addressing security issues at the community level, considering the engagement of youth in speech and online writing. In the article, the two sides of the issue were first described as how Facebook contributes to instilling violence in a peaceful area, and as well discussed how to resolve the crisis by using the same youth and media platforms. During this investigation, efforts were made to portray various scenarios from Facebook pages containing articles that would create confusion and those that would provide solutions. In addition, the youths were directly interviewed, some sections of the security agencies were contacted, and the results of the investigation were carefully presented conclusion was made. This work is based on the view of descriptive analysis of the View used by Jump up^ McArrthur (1992), Andrews, Jump up^ Janicki, Karol (2006), and Larry (2006).